Intersubband photoconductivity at 1.6 µm using a strain-compensated AlN/GaN superlattice - Baumann, Esther; Giorgetta, Fabrizio R.; Hofstetter, Daniel; Lu, H.; Chen, X.; Schaff, William J.; Eastman, L. F.; Golka, Sebastian; Schrenk, W.; Strasser, Gottfried (My University, 2005)
We report on intersubband absorption, photovoltaic, and photoconductive detection of near-infrared radiation in regular AlN/GaN superlattice structures. Photoconductive detection was achieved up to temperatures of 120 K. Simulation of the transition energies using a self-consistent Schrödinger-Poisson equation solver for our specific well width is in good agreement with the measurements. For a well width of 17 Å, the transition energy between ground state and first excited state in the GaN well is around 6300 cm–1 which corresponds to 1.6 µm.